CORPORATE SOCIAL RESPONSIBILITY di PT. PRUDENTIAL LIFE ASSURANCE - Ratu Annisa Fairuz; Faachira Faachira; Santoso Tri Raharjo; Risna Resnawaty (Prosiding Penelitian dan Pengabdian kepada Masyarakat, 2018)
ABSTRACTCorporate social responsibility program activities also vary, not only limited to social and economic programs. Social, education, and environment can be the target of corporate social responsibility. One company that applies corporate social responsibility is PT. Prudential Life Assurance. PT. Prudential Life Assurance was first established in 1995. Prudential was originally Prudential Plc, a financial services group from the United Kingdom with more than 160 years of experience. By combining Prudential's international experience in the field of life insurance with knowledge of local business procedures. Prudential has been in Indonesia since 1999 and has a commitment to develop its business in Indonesia. In accordance with these three things Prudential focuses its CSR activities in the fields of education, children, and disaster relief and prevention. Through the theme of "A Million Heart for A Millon Dreams" which has been around since September 2012, Prudential has a one million Indonesian mission that was achieved after two years of CSR programs at Prudential. PT. Prudential implements CSR programs only at the center, namely in Jakarta. The program consists of Chevening Scholarship, Financial Literacy, English Language Classes in Children's Prisons, Chairman's Challenge, Cha-Ching Money Smart Kids, and Clean Action. PT. Prudential Life Assurance provides assistance in the form of goods because it is more useful and useful. This study aims to explain the CSR programs and activities that have been carried out by PT. Prudential Life Assurance in Bandung. The type of method used in this study is a descriptive research method with a qualitative approach. Data collection techniques conducted by researchers in collecting data are through observation, interview, documentation, and a combination of the three.ABSTRAKKegiatan program corporate social responsibility pun beragam, tidak hanya terbatas pada program sosial maupun secara ekonomi. Sosial, pendidikan, dan lingkungan dapat dijadikan sasaran pertanggungjawaban sosial perusahaan. Salah satu perusahaan yang menerapkan corporate social responsibility adalah PT. Prudential Life Assurance. PT. Prudential Life Assurance didirikan pertama kali pada tahun 1995. Pada awalnya Prudential merupakan Prudential Plc, grup  jasa keuangan asal inggris dengan pengalaman lebih dari 160 tahun. Dengan menggabungkan pengalaman internasional Prudential di bidang asuransi jiwa dengan pengetahuan tata cara bisnis lokal. Prudential yang berada di Indonesia telaah ada sejak tahun 1999 dan memiliki komitmen untuk mengembangkan bisnisnya di Indonesia. Sesuai dengan ketiga hal tersebut Prudential memfokuskan kegiatan CSR-nya pada bidang pendidikan, anak-anak, serta bantuan dan pencegahan bencana. Melalui tema “A Million Heart for A Millon Dreams” yang ada sejak September tahun 2012, Prudential mempunyai misi satu juta orang Indonesia yang berhasil dicapai setelah dua tahun berjalannya program CSR di Prudential. PT. Prudential melaksanakan program CSR hanya di pusat saja yaitu di Jakarta. Program tersebut terdiri dari Chevening Scholarship, Financial Literacy, Kelas Bahasa Inggris di Lapas Anak, Chairman’s Challenge, Cha-Ching Money Smart Kids, dan Aksi Bersih. PT. Prudential Life Assurance memberikan bantuan berupa barang karena agar lebih berguna dan bermanfaat. Penelitian ini bertujuan untuk menjelaskan program maupun kegiatan CSR yang telah dilakukan PT. Prudential Life Assurance di Bandung. Jenis metode yang digunakan dalam penelitian ini adalah metode penelitian dekskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang dilakukan peneliti dalam mengumpulkan data ialah melalui teknik observasi, wawancara, dokumentasi, dan gabungan dari ketiganya.